The Relationship Between the Anxiety Level of Primiparous Mothers Who Are Not Accompanied by Their Husbands and the Duration of Labor - Dian Shofia Reny Setyanti; Nurhayani Nurhayani (International Journal Of Health Science, 2025)
In Indonesia, the main causes of maternal mortality are sepsis, abortion problems, prolonged labor, eclampsia, and hemorrhage. These causes of death have varying contributions, with sepsis (10%), hemorrhage (28%), which is often unpredictable and occurs suddenly, and prolonged labor (9%) contributing each. Psychological illness in pregnant women during pregnancy, environmental factors that trigger labor, and the high maternal mortality rate in Indonesia are contributing factors. This is undeniably due to the lack of support from various parties during pregnancy and childbirth, especially in the role of the family who inspires motivation during the labor process. It is very important to help mothers relax mentally. The purpose of this study was to investigate the correlation between the duration of labor and the level of anxiety experienced by first-time mothers who are not supported by their partners. A cross-sectional methodology was used in this study. A direct random sampling approach was used for sample collection. The relationship between the duration of labor and the level of anxiety was analyzed using the Spearman rank formula, which uses an ordinal scale for anxiety. The results of this study revealed a strong correlation between the level of anxiety experienced by first-time pregnant women who were not accompanied by their partners and the length of the labor process {Spearman rank: 0.515, p value: 0.004, OR: 4.867 (95% CI: 4.74-5.00)}.